COVID‐19 Aftershocks on Alcohol‐Associated Liver Disease: An Early Cross‐Sectional Report From the U.S. Epicenter - Stephanie M. Rutledge; Thomas D. Schiano; Sander Florman; Gene Y. Im (2021)
Experts have forewarned about the coronavirus disease 2019 (COVID-19) pandemic environment fomenting the rising incidence of alcohol use disorder (AUD) and alcohol-associated liver disease (ALD). We performed a cross-sectional study of ALD at our liver transplantation (LT) center, located in the initial U.S. epicenter, New York City. Centered around the "stay at home" order date in New York state, March 22, 2020, we defined three time periods: "pre-COVID" (January 1, 2020-March 21, 2020), "COVID-quarantine" (March 22, 2020-April 22, 2020), and "declining-COVID" (April 23, 2020-August 25, 2020). We found a 62% increase in interhospital patient transfers for ALD from pre-COVID (20 of 93, 21%) to the declining-COVID period (43 of 127, 34%). Our inpatient liver census with ALD also increased: 38% pre-COVID, 45% COVID-quarantine, and 49% declining-COVID. Among 30 patients with severe alcoholic hepatitis (AH) not responding to medical therapy since March 22, 2020, 9 underwent early LT for AH (16% of the total number of early LT during our 8-year program). Three of 9 early-LT recipients reported specific COVID-related stressors. All 25 previous LT recipients with established abstinence pre-COVID maintained abstinence at follow-up visits during the declining-COVID period. Of the 6 recipients with sustained alcohol use within 6 months before March 22, 2020, half regained abstinence during the declining-COVID period. Our findings help confirm the predictions of rising AUD and ALD as an immediate consequence of the COVID-19 pandemic. This aftershock particularly affected ethnically diverse patients with ALD with high inpatient mortality, reflecting the disproportionate impact of COVID-19 on underserved and minority populations. Alcohol relapse did not occur in long-term early LT for AH recipients during the time of COVID-19. This lends further support to AH being a viable indication for LT, with recipients able to demonstrate ongoing resilience in the face of this unprecedented universal stressor.